Factors Causing the Intention to Stop Smoking in Teenagers - Kurniawan, Afif; Tjokro, Silvia Haniwijaya; Sari, Etika Purnama; Geonarso, Roberto A (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background: the trend of teenagers hanging out with their friends nowadays is smoking. Many teenagers in Indonesia smoke because they are carried away by their environment. According to The Tobacco Control Atlas ASEAN Region 5th shows that Indonesia is the country with the highest number of smokers. The younger the smoking age, the longer the smoking habit. The longer a person's smoking habit, the greater the chance that person will get sick from smoking Aims: This study aims to look at factors from within adolescents to be able to bring up the intention to quit smoking. Methods: This study used a cross-sectional design. The sample selection used purposive technical sampling with a vulnerable age of 13-21 years. Logistic regression analysis was used to see whether there was a relationship between attitudes, subjective norms, perceptions, and self-efficacy towards the intention to quit smoking. Results: 30 teenagers were sampled in this study, aged 13-20 years, and the majority were in grade 3 of junior high school. Self-confidence or self-efficacy is the variable that has the greatest influence on the emergence of intention to stop smoking (0.000; 0.845). The existence of a very strong self-confidence to be able to quit smoking will bring up a very strong intention as well. Conclusion: smoking is an activity that is very detrimental to oneself and others. Many teenagers today since junior high school already have a smoking habit. Therefore, it is necessary to have a special method to bring out the intention of teenagers to quit smoking